The role of the village government performance and transparency in influencing village public trust - Muhammad Husni; Ratna Ayu Damayanti; Aini Indrijawati (Universitas Muhammadiyah Yogyakarta, Indonesia, 2023)
Research aims: This research examines the effect of transparency on the village community’s trust through village government performance as an intervening variable. Design/Methodology/Approach: The research was carried out using a survey method by distributing questionnaires to the village government in Jeneponto Regency, Indonesia. Totally, 196 questionnaires were filled in. Data analysis was then conducted by using Partial Least Square (PLS) approach. Research findings: The results revealed that the performance and transparency of the village government influenced public trust. The research emphasizes that the village government’s performance had an intervention role in the relationship between transparency and public trust. Theoretical contribution/Originality: This research discovers that performance plays a role as an intervening variable between transparency and public trust in the context of a village government study. Research limitation/Implication: The research was only conducted in the scope of Jeneponto Regency; therefore, the generalization capacity was limited.